Cancellation and uncertainty aversion on limit order books - Large, J (University of Oxford, 2004)
This paper models limit order books where each trader is uncertain of the underlying distribution in the asset's value to others. If this uncertainty is rapidly resolved, fleeting limit orders are submitted and quickly cancelled. This enhances liquidity supply, but leaves intact established comparative statics results on spreads. However, risk neutral liquidity suppliers are averse to persistent uncertainty due to concavity in the function describing limit order utility, and spreads widen. This helps explain wide spreads in the morning. The model describes traders who in equilibrium correctly anticipate market orders' endogenous stochastic intensities. It highlights how limit orders queue for execution.